Influence of dermatophytosis on quality of life: a cross sectional study from Kashmir Valley in North India - Bashir, Shahnawaz; Hassan, Iffat; T. Wani, Rabbanie (International Journal Of Community Medicine And Public Health, 2020)
Background: Over the past few years, dermatophytosis tends to be prolonged and persistent which negatively affects quality of life and relationship of patients with other people. There is limited literature available on the impact of dermatophytosis on the quality of life (QoL). The aim of the study is to investigate the influence of dermatophytosis on QoL in affected patients and identifying the risk factors associated therein. Methods: This was a cross-sectional study (descriptive study) in which 425 patients aged ≥18 years with dermatophytosis were included and evaluated for impact on QoL using dermatology life quality index (DLQI) questionnaire. Modified Kuppuswamy scale was also used for assessing the socioeconomic status of the study subjects. Independent t-test and ANOVA were used to find statistical associations between mean DLQI scores and various variables, wherever applicable. Results: The mean DLQI score in our study was 13.93±6.26. Dermatophytosis was found to have a very large effect on the QoL in majority (55.5%) of our subjects followed by moderate effect in 29.5% cases. Mean DLQI was higher in patients with longer duration of disease, involvement of unexposed sites (groins, gluteal region, axillae), greater number of sites involved, more body surface area involved, pruritus, redness and burning sensation (p<0.05). Regarding socio-demographic related variables, Mean DLQI score was higher in females, rural people, in (20-39) years age group, and in patients belonging to upper middle class (p<0.05). Conclusions: This study revealed significant impairment of QoL patients with dermatophytosis.